2004
DOI: 10.4049/jimmunol.172.12.7442
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 Regulates Expansion and Differentiation of Th1 Cells Following Induction of Peripheral T Cell Tolerance

Abstract: Intravenous treatment with Ag (peptide)-coupled, ethylene carbodiimide-fixed syngeneic splenocytes (Ag-SP) is a powerful method to induce anergy in vitro and peripheral T cell tolerance in vivo. In this study, we examined the effects of Ag-SP administration on T cell activity ex vivo and in vivo using OVA-specific DO11.10 TCR transgenic T cells. Although treatment with OVA323–339-SP resulted in a strong inhibition of peptide-specific T cell recall responses in vitro, examination of the immediate effects of Ag-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
(34 reference statements)
2
35
0
Order By: Relevance
“…Not surprisingly, costimulatory signals appear to play a dogmatic role in the regulation of Ag-SP tolerance induction. For example, low B7 expression on the donor-coupled cells is necessary for tolerance induction, while CTLA-4 is important for the maintenance phase of Ag-SP tolerance upon secondary encounter with Ag on stimulatory APCs expressing up-regulated levels of costimulatory molecules (14,15,24). Also, we have demonstrated that a chemical fixative, such as ECDI, is required during the coupling process (24,25).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Not surprisingly, costimulatory signals appear to play a dogmatic role in the regulation of Ag-SP tolerance induction. For example, low B7 expression on the donor-coupled cells is necessary for tolerance induction, while CTLA-4 is important for the maintenance phase of Ag-SP tolerance upon secondary encounter with Ag on stimulatory APCs expressing up-regulated levels of costimulatory molecules (14,15,24). Also, we have demonstrated that a chemical fixative, such as ECDI, is required during the coupling process (24,25).…”
Section: Discussionmentioning
confidence: 80%
“…Ag-SP is believed to render cells anergic due to a lack of costimulation (4). LPS-preactivated coupled cells with high B7 expression are incapable of inducing tolerance, suggesting that successful tolerance induction is dependent upon the lack of costimulatory signals coming from the APCs (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Walker et al (62) also showed in a diabetes model that the magnitude of the initial T cell expansion in the spleen was not significantly affected by the absence of CTLA-4, but that the subsequent accumulation of T cells in the pancreatic LNs and the development of diabetes were greatly enhanced in the KO. Finally, Eagar et al (63) recently published that CTLA-4 blockade solely in the ear was sufficient to allow the onset of delayed-type hypersensitivity effector function in a fixed cell, Ag presentation, tolerance model. From all these experiments, we and others (19) would conclude that CTLA-4 only acts as a brake on CD4 ϩ TCR-induced responses, including proliferation, cytokine production, and homing.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) and stimulates effector T-cell activation, expansion, function, and motility (5,6). blockade can also eliminate myeloid-derived suppressor cells (MDSC), which contributes to improving the survival of mice bearing ovarian tumors (7).…”
Section: Introductionmentioning
confidence: 99%